Long-term mortality in HIV-positive individuals virally suppressed for >3 years with incomplete CD4 recovery - Engsig, Frederik N; Zangerle, Robert; Katsarou, Olga; Dabis, Francois; Reiss, Peter; Gill, John; Porter, Kholoud; Sabin, Caroline; Riordan, Andrew; Fätkenheuer, Gerd; Gutiérrez, Félix; Raffi, Francois; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2014)
Some human immunodeficiency virus (HIV)-infected individuals initiating combination antiretroviral therapy (cART) with low CD4 counts achieve viral suppression but not CD4 cell recovery. We aimed to identify (1) risk factors for failure to achieve CD4 count >200 cells/µL after 3 years of sustained viral suppression and (2) the association of the achieved CD4 count with subsequent mortality.
Keywords: Adult; Anti-HIV Agents; Cause of Death; CD4 Lymphocyte Count; Cohort Studies; Female; Heterosexuality; HIV Infections; Humans; Logistic Models; Male; Middle Aged; Risk Factors; Substance-Related Disorders; Viral Load